Evaluation and Redesign of Faisal and Amman Streets - Omar Ismail; Mohammed Damiri; Ahmad Aryes (My University, 2016)
Nablus Government Compound is in the eastern side of Nablus City. Surrounding roads form the major entrance to Nablus, where vehicles come from Ramallah and other eastern cities and villages.           These roads are highways that have large traffic volumes due to existing governmental centers, schools, Al-Rawdah College, and presence of high commercial traffic. This leads to frequent loading and unloading as well as parking.           All of these facilities lead to a large volume of vehicles and pedestrians; therefore, creating a lot of conflicts, unclear movements, congestion, delay, and potential of crashes in this area.           This project aims to study this area, make an inventory, collect data for the traffic, and analyze it using the appropriate traffic software such as Highway Capacity Software and Synchro as well as geometric design for the approaches and intersections within the study area.           Based on evaluation of existing condition, suggestions for improvement are presented, which may include alternatives such as signalization of key intersections, geometric improvement, traffic control, etc.

. . . .   . () . .
Evaluation and Redesign of Faisal and Amman Streets